Prognosis of vulval cancer with lymph node status and size of primary lesion: A survival study - Pankaj Deka; Debabrata Barmon; Sushrata Shribastava; Amal Chandra Kataki; J D Sharma; M Bhattacharyya (Wolters Kluwer Medknow Publications, 2014)
Introduction: Squamous cell cancer of the vulva is a rare disease with an annual incidence of two to three per 100,000 women. Lymph node metastasis is the most important prognostic factor for the recurrence and survival in vulval carcinoma. Materials and Methods: It is a retrospective study of 18 cases, operated in our institute from 2006 to 2009 and followed up till July, 2012. These patients were divided into two group of node positive and node negative and compared for recurrence and survival. Result: Ten patients had lymph node metastasis and eight had no lymph node metastasis. Recurrence rate was 40% and 12.5% in node positive and negative groups, respectively. Adjuvant radiation when given to node negative bulky tumor showed no recurrence compared to one out of two in the non-irradiated group. Survival was only 25% in node positive recurrent cases. Conclusion: Lymph node positivity added a great risk for future recurrence. Prophylactic radiation in node negative, bulky tumor is helpful.